Functional Test Transformation to Improve Compaction - Bareiša, E.; Jusas, V.; Motiejūnas, K.; Šeinauskas, R. (Elektronika ir Elektrotechnika, 2008)
Compact test sets are very important for reducing the cost of testing the very large scale integrated circuits by reducing the test application time. In this work we presented a new procedure of functional static-based test transformation into functional delay test that allows improving test compaction. Experimental results for ISCAS’85 and ITC’99 benchmark circuits showed that the proposed approach reduced test size up to 4.83 times comparing with results presented in other publications whereas average test size reduction was up to 2.87 times. Ill. 3, bibl. 10 (in English; summaries in English, Russian and Lithuanian).